2018
DOI: 10.1016/j.snb.2018.06.122
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of methylmercaptan sensing response of WO3 semiconductor gas sensors by gas reactivity and gas diffusivity

Abstract: WO3-based semiconductor-type gas sensors were fabricated, and their sensing properties to methylmercaptan (CH3SH) were examined in this study. The Ru loading on WO3 was an effective way of an increase in the CH3SH response. In addition, the CH3SH response increased with a decrease in the operating temperature as well as with an increase in the thickness of the Ru-loaded WO3 sensing layer. The increase in the porosity of the Ru-loaded WO3 sensors, which were fabricated by utilizing polymethylmethacrylate micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The synthesized VWT particles had a diameter of several tens of nanometers, and no V-W-Ti-O composite oxide was It was found that at 300 • C, the 3 VWT gas sensor had good gas selectivity against H 2 gas and a high CH 3 SH response of 500 ppb (S = 1.74). This CH 3 SH response value is smaller than that of the WO 3 gas sensor in earlier reports [10,11]. In this study, the H 2 S, CH 3 SH, and H 2 gas response characteristics in dry atmosphere were measured only once.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The synthesized VWT particles had a diameter of several tens of nanometers, and no V-W-Ti-O composite oxide was It was found that at 300 • C, the 3 VWT gas sensor had good gas selectivity against H 2 gas and a high CH 3 SH response of 500 ppb (S = 1.74). This CH 3 SH response value is smaller than that of the WO 3 gas sensor in earlier reports [10,11]. In this study, the H 2 S, CH 3 SH, and H 2 gas response characteristics in dry atmosphere were measured only once.…”
Section: Discussionmentioning
confidence: 72%
“…Semiconductor-based gas sensors are effective for respiratory gas analysis from the standpoints of cost, compactness, and power consumption [6][7][8][9][10][11]. Su et al reported that for NO 2 sensing, a wearable, alveolus-inspired active membrane sensor based on the WO 3 system showed excellent selectivity and thermal and humidity stability [6].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, methyl mercaptan (CH 3 SH) is an important biomarker of halitosis as well. 35,36 Hence, we investigated the sensing response to methyl mercaptan and propanediol as interfering gases. In Figure S6 (Supporting Information), the response of 2.1 wt % NiO/WO 3 NPs to 100 ppm methyl mercaptan and 600 ppm propanediol is R a /R g = 1813, which is much lower than the response to H 2 S. Further, the long-term stability (see Figure 3f) of the 2.1 wt % NiO/WO 3 NP sensor to 10 ppm H 2 S was testified at 100 °C for 30 days, and the sensor showed excellent stability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, this material cannot address other limitations and cannot detect responses at the ppb or sub-ppm level [81]. In addition, experimental studies have found that methods including ion doping [82], modification using noble metals [83], hybridization with catalysts, and functionalization with sensing probes [84,85] or the use of heterostructures [86] can also improve gas sensing performance. Remaining challenges include the ability to further enhance selectivity for molecules with a similar sensing activity and dealing with interference with water vapor.…”
Section: Mofs-semiconducting Metal Oxides Composites 21 Sensing Mechanism Of Smox and Limitationsmentioning
confidence: 99%